Capital Structure and Profitability of Nepalese Hotel Industry (Research Journal of Padmakanya Multiple Campus, 2024)
Employing a descriptive and analytical quantitative research design, this study examines the influence of capital structure on the profitability of hotels in Nepal. The secondary data utilized in the research is obtained from the official websites of a limited number of hotels in Nepal. As independent variables, the Debt Ratio (DR), Short Term Debt Ratio (STDR), Liquidity Ratio (LR), and Firm Size (Size) are examined, while Return on Assets (ROA) and Return on Equity (ROE) are used as dependent variables. The relationship between these capital structure components and profitability metrics is analyzed using a multiple linear regression model. The study confirms the presumptions of the regression model as the residuals show homoscedasticity, independence and a normal distribution. Particularly the histogram of regression standardized residuals shows a bell-shaped curve, the Normal P-P Plot tightly aligns residuals with the diagonal line; and the scatterplot of residuals versus anticipated values shows a random distribution around the horizontal axis. These results validate the reliability and accuracy of the findings and support the use of linear regression in the research. Studies show that keeping the right balance between debt and equity may significantly increase a hotel's profitability. Larger companies may exploit their varied financial structures and have easier access to capital. The research contributes to the existing literature by offering practical insights for hotel managers and financial planners to make informed decisions about capital structure in order to achieve sustainable profitability and financial stability. It also provides empirical evidence from the Nepalese hotel industry.